Greater osteoblast proliferation on anodized nanotubular titanium upon electrical stimulation - Batur Ercan (Dove Medical Press, 2008)
Batur Ercan1, Thomas J Webster1,21Division of Engineering, Brown University, Providence, RI, USA; 2Department of Orthopedic Surgery, Brown University, Providence, RI, USAAbstract: Currently used orthopedic implants composed of titanium have a limited functional lifetime of only 10–15 years. One of the reasons for this persistent problem is the poor prolonged ability of titanium to remain bonded to juxtaposed bone. It has been proposed to modify titanium through anodization to create a novel nanotubular topography in order to improve cytocompatibility properties necessary for the prolonged attachment of orthopedic implants to surrounding bone. Additionally, electrical stimulation has been used in orthopedics to heal bone non-unions and fractures in anatomically difficult to operate sites (such as the spine). In this study, these two approaches were combined as the efficacy of electrical stimulation to promote osteoblast (bone forming cell) density on anodized titanium was investigated. To do this, osteoblast proliferation experiments lasting up to 5 days were conducted as cells were stimulated with constant bipolar pulses at a frequency of 20 Hz and a pulse duration of 0.4 ms each day for 1 hour. The stimulation voltages were 1 V, 5 V, 10 V, and 15 V. Results showed for the first time that under electrical stimulation, osteoblast proliferation on anodized titanium was enhanced at lower voltages compared to what was observed on conventional (nonanodized) titanium. In addition, compared to nonstimulated conventional titanium, osteoblast proliferation was enhanced 72% after 5 days of culture on anodized nanotubular titanium at 15 V of electrical stimulation. Thus, results of this study suggest that coupling the positive influences of electrical stimulation and nanotubular features on anodized titanium may improve osteoblast responses necessary for enhanced orthopedic implant efficacy.Keywords: titanium, anodization, nanotubular, electrical stimulation, osteoblast, proliferation